Istinbātu Al-Qowā’idi Wa Al-Dawābiti Al-Uṣuliyyaħ Wa Al-Fiqhiyyaħ Min Kitābi Al-Hāwī Lilmāwaridī: استنباط القواعد والضوابط الأصولية والفقهية من كتاب الحاوي للماوردي - Saket, Saeed Abdullah Saeed (PT. Student Rihlah Indonesia, 2024)
This research uses qualitative approach and literature review method. Based on the results of the study, these rules are fundamentalist, jurisprudential rules, and some of them are control and not rules. The use of rules in controlling jurisprudence and compiling and perfecting its problems. Al-Mawardi relied on his rule on the doctrine of Al-Shafi'i (may Allah have mercy on him). Al-Shafi'i himself violated the jurisprudence or ground rules he decided.